2006
DOI: 10.1007/s10517-006-0361-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-term mental and pain stress on the dynamics of H4 histone acetylation in hippocampal neurons of rats with different levels of nervous system excitability

Abstract: Priority data on specific effect of long-term mental and pain stress on the dynamics of H4 histone acetylation in the pyramidal neuron nuclei of the hippocampal CA3 field in rats selected by the nervous system excitability were obtained using a comparative genetic method. The congruency of long-term post-stress modification of H4 histone acetylation in neurons of rats with high threshold excitability and behavioral changes intrinsic of these rats suggest that increased acetylation of H4 histone together with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 2 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…Histone modifications have been implicated in broad neurobiological processes such as development of the CNS (reviewed in MacDonald and Roskams, 2009), post-traumatic stress disorders (Sokolova et al, 2006), childhood abuse/suicide (Meaney et al, 2007; McGowan et al, 2009), memory formation (Gupta et al, 2010), and addiction (Impey, 2007); specific physiologic processes such as neuronal differentiation (Kular et al, 2009), regulation of choline acetyltransferase activity (Aizawa and Yamamuro, 2010), astrocyte GDNF and BDNF transcription (Wu et al, 2008), microglial apoptosis (Chen et al, 2007), and axon pathfinding (Zinovyeva et al, 2006); and various neurologic disorders, including Parkinson’s disease (Chen et al, 2007; Wu et al, 2008), motor neuron disease (reviewed in Echaniz-Laguna et al, 2008), multiple sclerosis (reviewed in Gray and Dangond, 2006), X-linked mental retardation (Tahiliani et al, 2007), and stroke/cerebral palsy (Meisel et al, 2006). All of these histone-related processes occur in the context of the CNS, and many have been reported to function as dynamic regulatory mechanisms in postmitotic neurons.…”
Section: 0 Dynamic Epigenetic Regulation In Adult Neuronsmentioning
confidence: 99%
“…Histone modifications have been implicated in broad neurobiological processes such as development of the CNS (reviewed in MacDonald and Roskams, 2009), post-traumatic stress disorders (Sokolova et al, 2006), childhood abuse/suicide (Meaney et al, 2007; McGowan et al, 2009), memory formation (Gupta et al, 2010), and addiction (Impey, 2007); specific physiologic processes such as neuronal differentiation (Kular et al, 2009), regulation of choline acetyltransferase activity (Aizawa and Yamamuro, 2010), astrocyte GDNF and BDNF transcription (Wu et al, 2008), microglial apoptosis (Chen et al, 2007), and axon pathfinding (Zinovyeva et al, 2006); and various neurologic disorders, including Parkinson’s disease (Chen et al, 2007; Wu et al, 2008), motor neuron disease (reviewed in Echaniz-Laguna et al, 2008), multiple sclerosis (reviewed in Gray and Dangond, 2006), X-linked mental retardation (Tahiliani et al, 2007), and stroke/cerebral palsy (Meisel et al, 2006). All of these histone-related processes occur in the context of the CNS, and many have been reported to function as dynamic regulatory mechanisms in postmitotic neurons.…”
Section: 0 Dynamic Epigenetic Regulation In Adult Neuronsmentioning
confidence: 99%
“…The HC is particularly susceptible to structural, functional, and neurogenic rearrangements in response to environmental stimuli [13][14][15]. Several research groups have reported evidence that these alterations are regulated by epigenetic processes, defined as inheritable states of gene activity not based on changes in DNA sequence [16][17][18]. One of the major epigenetic mechanisms is DNA cytosine methylation [19].…”
Section: Introductionmentioning
confidence: 99%
“…In the hippocampus, evidence that histone modifications might play a significant role in the function of the structure came from the work of Weaver (11), who showed that differences in maternal behavior produced differences in the behavior of offspring, and that this difference was associated with changes in histone acetylation, and could be blocked by a histone deacetylase inhibitor. Subsequent work has connected acetylation of histone H4 (12) and acetylation, phosphorylation and methylation of H3 in the hippocampus with stress (13)(14)(15). Histone lysine methylation, unlike acetylation, for example, is remarkable for the site specificity of its associated machinery and its ability to recruit specific effector protein complexes (16)(17)(18).…”
mentioning
confidence: 99%